Modelling the sprouting capacity from underground buds of the perennial weed Sonchus arvensis. (19th June 2018) - Taab, A; Andersson, L; Boström, U
Summary: Sonchus arvensis is a problematic perennial weed species causing problems in many crops. Control measures often rely on soil tillage or mowing; both methods are used to exhaust the root system. This approach fails during periods of restrictions in sprouting capacity or shoot regrowth. The aim of this study was to develop a simulation model for prediction of shoot sprouting capacity in underground buds of S. arvensis . We hypothesised restricted regrowth to be induced as a function of photoperiod and temperature sum and released as a function of cold temperature sum. The model was parameterised and calibrated against observations of shoot regrowth from an experiment on intact roots of S. arvensis . Subsequently, it was validated against observations of regrowth from another experiment on intact roots and sprouting from fragmented roots from a third experiment. Restriction in regrowth was attributed to reduction in the photoperiod, observed when the day length decreased below a threshold of 16.5 h, but also to a daily mean temperature below 16.8°C. Resumed regrowth occurred in late autumn at a daily mean temperature threshold of 4.7°C. The pattern of changes over time in shoot regrowth from an intact root system was well predicted by the model. The temporal change in sprouting capacity from buds on fragmented roots followed the same pattern, but with a quantitative difference between the model prediction and the observed sprouting capacity. We conclude that the model can be used to predict the pattern over time of sprouting capacity in intact roots of S. arvensis .